A escrita de si como relação subjetiva e inscrição ética do sujeito surdo - Morais, Mariana Peres de (Universidade Federal de São Carlos, 2023)
Deaf education has been a very relevant topic in recent decades in our country, especially due to the current discussion about inclusive practices. However, it is noted that the advances made in the teaching of deaf people still require investments, resources and effective policies that guarantee the access and permanence of this public in the school environment. Among these issues, the current academic literature has shown great interest regarding the process of learning the Portuguese language for the deaf public. However, even though it is a challenge for the school, there are cases of deaf people who use the materiality of the Portuguese language and/or sign language in a very significant way to the point of expressing themselves through registration (written in Portuguese or in videos in Libras) about their memories, organization of thoughts, among other ways in everyday life in order to lead to what is defended by a writing of the self, in the philosophical-foucauldian conception. The investigation of the factors that mobilize the deaf to use self-writing as a tool for the subjectivation process is still a little explored field. In this sense, the general objective of this study is to investigate the deaf utterances produced through a self-writing that mobilize the construction of the subjectivation process of the deaf subject, from a methodology based on the principles of Foucauldian genealogical perspective combined with cartography. Such paths will be followed to search for records of narrative discourses in social networks and analyzed in the light of the philosophies of differences. The hypothesis is that bilingual deaf subjects (Libras and Portuguese Language - LP), in the act of making the record a space of reflexive expansion to constitute themselves, transit between these records, oscillating between LP and Libras, which are chosen by the deaf depending on who he imagines to be his possible reader. Therefore, the thesis is that the writing of the self is a space for the creation of an aesthetics of existence and that in contemporary times can be manifested by social networks, which have been used for exchanges of the self with the other and, the change of linguistic register by the deaf, refers both to the supposed reader addressed and to the theme on which there is the reflection produced by the author. Trying to understand the aspects that make it possible to write from the self, regardless of the linguistic modality, can contribute to the development of more extensive and productive discussions that seek to understand about the appropriation of deaf writing, in addition to reflecting on the elements providers for educational proposals suggested for the teaching of the deaf so that they come to relate in a pleasant way with the Portuguese language and, thus, transform the negative historical image that has been imposed by society and that often strengthens barriers to communication between deaf and listeners.
Self-writing as a subjective relationship and ethical inscription of the deaf subject
La autoescritura como relación subjetiva e inscripción ética del sujeto sordo
Keywords: Educação especial; Língua brasileira de sinais; Língua portuguesa; Surdos; CIENCIAS HUMANAS::EDUCACAO::CURRICULO; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM; CIENCIAS HUMANAS::EDUCACAO::ORIENTACAO E ACONSELHAMENTO; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO; ENGENHARIAS; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM::METODOS E TECNICAS DE ENSINO; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM::TECNOLOGIA EDUCACIONAL; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM::TEORIAS DA INSTRUCAO; CIENCIAS HUMANAS::EDUCACAO::FUNDAMENTOS DA EDUCACAO::FILOSOFIA DA EDUCACAO; LINGUISTICA, LETRAS E ARTES::LINGUISTICA; LINGUISTICA, LETRAS E ARTES::LINGUISTICA::SOCIOLINGUISTICA E DIALETOLOGIA; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO DE ADULTOS